Un cadre théorique et méthodologique pour l’observation des pratiques collaboratives des maîtres E - Corinne Mérini; Serge Thomazet; Pascale Ponté (Recherches en Éducation)
Methodology of observation cannot be separated from the position of the researcher, the standpoint he adopts to observe, the history of the construction of the object and the way this object takes place in the profession. Relying on the work of a specialist teacher « maître E », and especially of the part of his job that rely him with colleagues, parents and professionals, we explore in this paper the methodological question of observation of collaborative practices of this teachers who are not in charge of a classroom. These practices leave an important part to context effects and requires the researcher to rethink the unit of observation, the conditions of access to specific information, as well as crossing of diversified data (professional writings, video recordings, self-confrontation interviews…), with a sufficient longitudinally. The special characteristics of collaborative practices led us to diversify triangulations. Finally, we point limitations of our work.